Efeitos de intervenção por telefone na adesão ao exame mamográfico: ensaio clínico randomizado - Ramos, Altamira Mendonça Félix Gomes (2023)
Mammography is considered the most effective exam in the early detection of breast cancer. Studies indicate that women's adherence to this treatment increases the chances of cure. The objective was to test the effects of an educational intervention by telephone on women's adherence to screening mammography. A randomized clinical trial was carried out in a teaching hospital in North eastern Brazil. The study population consisted of women who were undergoing a gynecological consultation at the outpatient clinic of this location. Women over 50 years of age were included, who had not had a mammogram for at least two years and who had a landline or mobile telephone. The formula for studies with comparative groups was used for sample calculation. The randomization of the sample was carried out by a sequence of random numbers generated by computer, with each participant being allocated to the comparison or intervention group according to the generated sequence. In this research, care was taken that the study participants did not know which group they belonged to. The professionals who worked in the gynecological consultation also did not know which group the women belonged to. The main researcher knew the names and contacts of the participants in the intervention group and applied the educational intervention and the scale after the first contact. Data collection took place in two moments and the intervention group received a telephone call during this period with the use of an educational strategy about mammography based on the principles of motivational interviewing. The comparison group received standard gynecological consultation care. The first contact was at the gynecological consultation where a sociodemographic questionnaire and the Champion's Health Belief Model Scale were applied. Participants were informed that they could receive a call after the first contact and that they would receive another call in which the Champion's Health Belief Model Scale would be applied again. Data were tabulated, analysed and displayed in tables and graphs. The project was approved by the ethics committee with opinion No. 3,937,642. According to the results, before the educational intervention, the intervention group had a total of 24.32% of adherence, as well as the comparison group. In the second moment of application of the scale, this percentage was 88.88% of adherence in the intervention group and 60% in the comparison group. Even after the educational intervention, the numbers were higher in terms of adherence in the comparison group than in the intervention group, in the second moment of applying the scale, in which the percentage of adherence was 38.88% for the intervention group and 60% for the intervention group. for the comparison group, taking into account the general scale. The only variable with a significant association, using Pearson's chi-square test, was the age group between 50 and 59 years with the adherence factor before the educational intervention. The educational intervention by telephone was not effective in the adherence of women to the mammography exam. More studies are needed to evaluate the adherence of women to mammography after non-conventional interventions in the population.